After Atalese, New Jersey Opinions Are Limiting Enforcement of Arbitration Provisions. Issue 8 (September 2016) - Albert, Daniela; Heifetz, Elizabeth; Bleemer, Russ
Abstract : Arbitration contract enforcement has been in flux in New Jersey since the state's Supreme Court passed down Atalese v. U.S. Legal Services LP, 219 N.J. 430, 99 A.3d 306 (2014), cert. denied, 135 S. Ct. 2804, 192 L. Ed. 2d 847 (2015)(available athttp://bit.ly/ZtfbW4 ).